2017
DOI: 10.1159/000484256
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Review of the Diagnostic and Management Challenges of Mirizzi Syndrome at the Singapore General Hospital

Abstract: Background: Mirizzi syndrome (MS) occurs when gallstone impaction in Hartmann’s pouch results in extrinsic obstruction of the common bile duct, and fistulation may occur. Methods: We retrospectively reviewed electronic records of patients surgically treated for MS from November 2001 to June 2012. Patient presentations, diagnostic methods, treatments and complications were recorded. Results: Sixty-four patients were grouped according to a classification proposed by Beltran et al. [World J Surg 2008; 32: 2237–22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Mirizzi syndrome (MS) is an uncommon phenomenon, with an incidence of 0.7-2.9% of all cholecystectomies (2,4,5). Pablo Luis Mirizzi first described this entity in 1948, defining it as an obstruction of the common hepatic duct (CHD) or common bile duct (CBD) by the compression of an impacted stone in the neck of the gallbladder or cystic duct, causing obstructive jaundice, and leading occasionally to fistulization to the bile duct or surrounding organs (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Mirizzi syndrome (MS) is an uncommon phenomenon, with an incidence of 0.7-2.9% of all cholecystectomies (2,4,5). Pablo Luis Mirizzi first described this entity in 1948, defining it as an obstruction of the common hepatic duct (CHD) or common bile duct (CBD) by the compression of an impacted stone in the neck of the gallbladder or cystic duct, causing obstructive jaundice, and leading occasionally to fistulization to the bile duct or surrounding organs (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…According to the original papers, the most common symptoms were abdominal pain (incidence 65.7-100%) and jaundice (ranging between 45-87.5%). Other symptoms were nausea and vomiting (31-62%), cholangitis (up to 56%), fever (21-42%) and anorexia (11-29.2%) [6,7,[28][29][30][31][32]. Furthermore, Shirah et al reported that there was a positive Murphy's sign in 50% of their patients during physical examination [6].…”
Section: Symptoms and Laboratory Resultsmentioning
confidence: 99%
“…CT scan is useful in differentiating Mirizzi syndrome from a malignancy, especially when a cholecystobiliary fistula is present [14]. Pre-operative diagnosis improves outcomes of surgery, allowing better planning [5,6,8,[27][28][29] and referral to the appropriate surgeon. If pre-operative diagnosis is not achieved, intra-operative recognition and proper management are essential to improve outcomes, reduce morbidity (up to 17% bile duct injury) and mortality [5,13].…”
Section: Discussionmentioning
confidence: 99%
“…The traditional approach for type II Mirizzi syndrome included a subtotal cholecystectomy leaving a 10 mm flap of gallbladder around the fistula for the reconstruction of the destroyed bile duct protected by a T-Tube to avoid post-operative strictures or bile leakages. In cases with large defects (> 50% of the circumference of the CBD) when the surrounding tissues cannot be recruited to reconstruct the CBD bilioenteric anastomosis may be required [3,5,28] (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%